Ethics - Pasco, Marc Oliver D; Suarez, V. Fullente ; Rodriguez, Agustin Martin G. (Quezon City, 2018)
A guide to ethical reflection, Ethics provides the Filipino students with a framework for appreciating what human civilizations have come to understand as the good and how this understanding shapes their human flourishing. It aims to help students understand that the quest for ethical norms for living a full life is an evolving task that they have to engage in and realize
Keywords: Ethics